Workplace Emissions and Exposures During Semiconductor Nanowire Production, Post-production, and Maintenance Work. Issue 1 (10th December 2019) - Isaxon, Christina; Lovén, Karin; Ludvigsson, Linus; Sivakumar, Sudhakar; Gudmundsson, Anders; Messing, Maria E; Pagels, Joakim; Hedmer, Maria
Abstract: Background: Nanowires are a high-aspect-ratio material of increasing interest for a wide range of applications. A new and promising method to produce nanowires is by aerotaxy, where the wires are grown in a continuous stream of gas. The aerotaxy method can grow nanowires much faster than by more conventional methods. Nanowires have important properties in common with asbestos fibers, which indicate that there can be potential health effects if exposure occurs. No conclusive exposure (or emission) data from aerotaxy-production of nanowires has so far been published. Methods: Different work tasks during semiconductor nanowire production, post-production, and maintenance were studied. A combination of direct-reading instruments for number concentration (0.007–20 µm) and filter sampling was used to assess the emissions (a couple of centimeter from the emission sources), the exposure in the personal breathing zone (max 30 cm from nose–mouth), and the concentrations in the background zone (at least 3 m from any emission source). The filters were analyzed for metal dust composition and number concentration of nanowires. Various surfaces were sampled for nanowire contamination. Results: The particle concentrations in the emission zone (measured with direct-reading instruments) were elevated during cleaning of arc discharge, manual reactor cleaning, exchange of nanowire outflow filters, and sonication of substrates with nanowires. In the case of cleaning of the arc discharge and manual reactor cleaning, the emissions affected the concentrations in the personal breathing zone and were high enough to also affect the concentrations in the background. Filter analysis with electron microscopy could confirm the presence of nanowires in some of the air samples. Conclusions: Our results show that a major part of the potential for exposure occurs not during the actual manufacturing, but during the cleaning and maintenance procedures. The exposures and emissions were evaluated pre- and post-upscaling the production and showed that some work tasks (e.g. exchange of nanowire outflow filters and sonication of substrates with nanowires) increased the emissions post-upscaling.